TRPV4 Role in Neuropathic Pain Mechanisms in Rodents - Patrícia Rodrigues; Náthaly Andrighetto Ruviaro; Gabriela Trevisan (MDPI AG, 2022)
Neuropathic pain is a chronic pain caused by a disease or damage to the somatosensory nervous system. The knowledge about the complete mechanisms is incomplete, but the role of oxidative compounds has been evaluated. In this context, we highlight the transient potential receptor vanilloid 4 (TRPV4), a non-selective cation channel, that can be activated by oxidated compounds. In clinical trials, the TRPV4 antagonist (GSK2798745) has been well-tolerated in healthy volunteers. The TRPV4 activation by oxidative compounds, such as hydrogen peroxide (H2O2) and nitric oxide (NO), has been researched in neuropathic pain models. Thus, the modulation of TRPV4 activation by decreasing oxidated compounds could represent a new pharmacological approach for neuropathic pain treatment. Most models evaluated the TRPV4 using knockout mice, antagonist or antisense treatments and detected mechanical allodynia, hyposmotic solution-induced nociception and heat hyperalgesia, but this channel is not involved in cold allodynia. Only H2O2 and NO were evaluated as TRPV4 agonists, so one possible target to reduce neuropathic pain should focus on reducing these compounds. Therefore, this review outlines how the TRPV4 channel represents an innovative target to tackle neuropathic pain signaling in models induced by trauma, surgery, chemotherapy, cancer, diabetes and alcohol intake.